2014
DOI: 10.1016/j.bbadis.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-response protein prostate-associated gene 4, interacts with c-Jun and potentiates its transactivation

Abstract: The Cancer/Testis Antigen (CTA), Prostate-associated Gene 4 (PAGE4), is a stress-response protein that is upregulated in prostate cancer (PCa) especially in precursor lesions that result from inflammatory stress. In cells under stress, translocation of PAGE4 to mitochondria increases while production of reactive oxygen species decreases. Furthermore, PAGE4 is also upregulated in human fetal prostate, underscoring its potential role in development. However, the proteins that interact with PAGE4 and the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 69 publications
6
65
0
Order By: Relevance
“…FRET measurements repeated here had FRET efficiency of 0.55 (A18:C63) and 0.65 (C63:P102) for WT-PAGE4 and FRET efficiency of 0.52 (A18: C63) and 0.65 (C63:P102) for HIPK1-PAGE4. These smFRET values were consistent with our previous studies (32,37). Using the same labeling sites with CLK2-PAGE4, we found FRET efficiency of 0.35 (A18:C63) and 0.58 (C63:P102).…”
Section: Hyperphosphorylation Of Page4 Shifts the Conformational Ensesupporting
confidence: 92%
See 4 more Smart Citations
“…FRET measurements repeated here had FRET efficiency of 0.55 (A18:C63) and 0.65 (C63:P102) for WT-PAGE4 and FRET efficiency of 0.52 (A18: C63) and 0.65 (C63:P102) for HIPK1-PAGE4. These smFRET values were consistent with our previous studies (32,37). Using the same labeling sites with CLK2-PAGE4, we found FRET efficiency of 0.35 (A18:C63) and 0.58 (C63:P102).…”
Section: Hyperphosphorylation Of Page4 Shifts the Conformational Ensesupporting
confidence: 92%
“…We had previously observed that PAGE4 phosphorylated by HIPK1 prefers a more compact conformation relative to the WT PAGE4 ensemble (37) and potentiates transactivation of c-Jun in a cell-based transactivation assay using a luciferase reporter (32). Therefore, we determined the effect of hyperphosphorylation of PAGE4 on c-Jun potentiation using the same luciferase reporter assay in PC3 cells that were cotransfected with full-length human CLK2 cDNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations